Inhibiting post-translational core fucosylation prevents vascular calcification in the model of uremia. (October 2016) - Wen, Xinyu; Liu, Anqi; Yu, Changqing; Wang, Lingyu; Zhou, Mengying; Wang, Nan; Fang, Ming; Wang, Weidong; Lin, Hongli
Highlights: Significant increases in levels of Fut8 (an essential enzyme for core fucosylation), core fucose and TGFβ/smad2/3 signaling pathway in uremic vascular calcification. siRNA-mediated knockdown of Fut8 attenuated vascular calcification. The TGFβ/smad2/3 signaling pathway is regulated by Fut8-mediated core fucosylation. Abstract: Vascular calcification (VC) is an independent risk factor for cardiovascular disease and mortality in uremia. Post-translational core fucosylation is implicated in a number of pathological processes. First, we investigated the role of core fucosylation and key TGF-β1 pathway receptors in calcified arteries in vivo . To determine whether blocking core fucosylation effectively inhibited VC and TGF-β/Smad signaling pathway, we established an in vitro model of phosphate-induced calcification in rat vascular smooth muscle cells (VSMCs) to assess the role of core fucosylation in VC. Core fucose could be detected at markedly higher levels in calcified VSMCs than control cells. Fut8 (α-1, 6 fucosyltransferase), the only enzyme responsible for core fucosylation in humans, was significantly upregulated by high phosphate. Exposed to high phosphate media and blocking core fucosylation in VSMCs by knocking down Fut8 using a siRNA markedly reduced calcium and phosphorus deposition and Cbfα1 expression (osteoblast-specific transcription factor), and increased α-Sma expression (smooth muscle cell marker). Fut8 siRNA significantly inhibited TGF-β/Smad2/3 signaling activation in VSMCs cultured in high phosphate media. In conclusion, this study provides evidence to suggest core fucosylation plays a major role in the process of VC and appropriate blockade of core fucosylation may represent a potential therapeutic strategy for treating VC in end-stage renal disease.